2018
DOI: 10.1155/2018/9026847
|View full text |Cite
|
Sign up to set email alerts
|

Past Results, Present Trends, and Future Challenges in Intrabody Communication

Abstract: Intrabody communication (IBC) is a wireless communication technology using the human body to develop body area networks (BANs) for remote and ubiquitous monitoring. IBC uses living tissues as a transmission medium, achieving power-saving and miniaturized transceivers, making communications more robust against external interference and attacks on the privacy of transmitted data. Due to these advantages, IBC has been included as a third physical layer in the IEEE 802.15.6 standard for wireless body area networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 212 publications
(382 reference statements)
1
61
0
Order By: Relevance
“…For instance, samples with low oil solution concentration can be utilized for mimicking tissue with high dielectric permittivity, while samples with high oil solution concentration can be used to mimic tissues with low conductivity like cortical bone, as shown in Figures As shown in Figures 6 and 7, the electrical properties of different tissues can be matched with samples of certain formulations and concentrations, depending on the electrical property of interest (whether conductivity or permittivity is more of concern), and the range of frequency in which the IBC application will operate within. It is important to note that most IBC applications utilize less than 1 MHz of bandwidth [22], due to the nature of medical applications, that typically require low bit rates. A summary of such results; best matching samples (samples that shows less than 10 % matching error) with respect to different tissues, regarding conductivity and permittivity, for different frequency ranges (Fmin is the minimum frequency and Fmax is the maximum frequency in MHz defining the band over which the matching error is below 10% ) within the IBC application band, is provided in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, samples with low oil solution concentration can be utilized for mimicking tissue with high dielectric permittivity, while samples with high oil solution concentration can be used to mimic tissues with low conductivity like cortical bone, as shown in Figures As shown in Figures 6 and 7, the electrical properties of different tissues can be matched with samples of certain formulations and concentrations, depending on the electrical property of interest (whether conductivity or permittivity is more of concern), and the range of frequency in which the IBC application will operate within. It is important to note that most IBC applications utilize less than 1 MHz of bandwidth [22], due to the nature of medical applications, that typically require low bit rates. A summary of such results; best matching samples (samples that shows less than 10 % matching error) with respect to different tissues, regarding conductivity and permittivity, for different frequency ranges (Fmin is the minimum frequency and Fmax is the maximum frequency in MHz defining the band over which the matching error is below 10% ) within the IBC application band, is provided in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Several trials were reported in literature for the use of phantoms for IBC applications as a stable and easy to control, yet accurate experimental setup [22], [23]. Liquid phantoms were usually adopted in these trials, being the easiest to prepare.…”
Section: A Phantoms For Ibcmentioning
confidence: 99%
“…The pioneering work of Zimmerman on BCC was motivated by the dream and the imagination of a digital interconnected world where the center of communication is the human being [1], [2]. Driven by this idea, BCC can be established relying on two main coupling mechanisms [3]. The signal can be coupled in the body by direct current injection (galvanic coupling -GC) from a transmitter (TX) electrode to a receiver (RX).…”
Section: Introductionmentioning
confidence: 99%
“…The signal can be coupled in the body by direct current injection (galvanic coupling -GC) from a transmitter (TX) electrode to a receiver (RX). Alternatively, the near-field coupling of a quasi-electrostatic field between TX and RX electrodes can be used for (capacitive coupling -CC) [3]- [9]. However, the possibility of conveying information in the sub-cutaneous fat at frequencies around 2.45 GHz is currently under investigation [10]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…Intra-body communications can be categorized into two main types; capacitive coupling (near-field coupling method) and galvanic coupling [13][14][15][16][17][18]. In capacitive coupling, only the signal electrodes of the transmitter and the receiver are attached to the body while the ground (GND) electrodes are left floating in the air.…”
Section: Introductionmentioning
confidence: 99%